Multiscale Spatial Analysis of Headwater Vulnerability in South-Central Chile Reveals a High Threat Due to Deforestation and Climate Change - Vergara-Egert, P; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier B.V., 2022)
Headwaters represent an essential component of hydrological, ecological, and socioeconomical systems, by providing constant water streams to the complete basin. However, despite the high importance of headwaters, there is a lack of vulnerability assessments worldwide. Identifying headwaters and their vulnerability in a spatially explicit manner can enable restauration and conservation programs. In this study, we assess the vulnerability of headwaters in South-Central Chile (38.4 to 43.2°S) considering multiple degradation factors related to climate change and land cover change. We analyzed 2292 headwaters, characterizing multiple factors at five spatial scales by using remote sensing data related to Land Use and Cover Change (LUCC), human disturbances, vegetation cover, climate change, potential water demand, and physiography. We then generated an index of vulnerability by integrating all the analyzed variables, which allowed us to map the spatial distribution of headwater vulnerability. Finally, to estimate the main drivers of degradation, we performed a Principal Components Analysis with an Agglomerative Hierarchical Clustering, that allowed us to group headwaters according to the analyzed factors. The largest proportion of most vulnerable headwaters are located in the north of our study area with 48.1 %, 62.1 %, and 28.1 % of headwaters classified as highly vulnerable at 0, 10, and 30 m scale, respectively. The largest proportion of headwaters are affected by Climate Change (63.66 %) and LUCC (23.02 %) on average across all scales. However, we identified three clusters, in which the northern cluster is mainly affected by LUCC, while the Andean and Coastal clusters are mainly affected by climate change. Our results and methods present an informative picture of the current state of headwater vulnerability, identifying spatial patterns and drivers at multiple scales. We believe that the approach developed in this study could be useful for new studies in other zones of the world and can also promote Chilean headwater conservation. © 2022 Elsevier B.V.